2021
DOI: 10.1038/s41467-021-27537-5
|View full text |Cite
|
Sign up to set email alerts
|

Uppermost crustal structure regulates the flow of the Greenland Ice Sheet

Abstract: The flow of the Greenland Ice Sheet is controlled by subglacial processes and conditions that depend on the geological provenance and temperature of the crust beneath it, neither of which are adequately known. Here we present a seismic velocity model of the uppermost 5 km of the Greenlandic crust. We show that slow velocities in the upper crust tend to be associated with major outlet glaciers along the ice-sheet margin, and elevated geothermal heat flux along the Iceland hotspot track inland. Outlet glaciers p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(31 citation statements)
references
References 72 publications
0
31
0
Order By: Relevance
“…The elliptcity curves were then inverted using the Monte-Carlo based Neighbourhood Algorithm (Sambridge, 1999) to generate 1-D seismic shear-wave velocity (Vs) profiles directly beneath each station. Jones and others (2021) showed that low seismic velocities correlate with large glaciers of Jakobshavn, Helheim and Kangerdlussuaq and regions of elevated heat flux as proposed by Martos and others (2018). Jones and others (2021) inferred that the low seismic velocities within the interior of the ice sheet are the subglacial expression of the Iceland hotspot track that traversed Greenland ∼80−50 Ma and controls the onset of fast ice flow for the North East Greenland Ice Stream and Petermann Glacier.…”
Section: Characterisation Of the Subglacial Geologymentioning
confidence: 53%
See 4 more Smart Citations
“…The elliptcity curves were then inverted using the Monte-Carlo based Neighbourhood Algorithm (Sambridge, 1999) to generate 1-D seismic shear-wave velocity (Vs) profiles directly beneath each station. Jones and others (2021) showed that low seismic velocities correlate with large glaciers of Jakobshavn, Helheim and Kangerdlussuaq and regions of elevated heat flux as proposed by Martos and others (2018). Jones and others (2021) inferred that the low seismic velocities within the interior of the ice sheet are the subglacial expression of the Iceland hotspot track that traversed Greenland ∼80−50 Ma and controls the onset of fast ice flow for the North East Greenland Ice Stream and Petermann Glacier.…”
Section: Characterisation Of the Subglacial Geologymentioning
confidence: 53%
“…The method assumes that the Rayleigh wave particle motion is retrograde permitting the calculation of the back azimuth of the signal from the station to the source (Schimmel and others, 2011;Sergeant and others, 2013;Berbellini and others, 2019). Finally, the ellipticity of the extracted Rayleigh waves is estimated as a function of frequency and can subsequently be used in inversions for subsurface structure (e.g., Berbellini and others, 2019;Jones and others, 2021) 3. Current applications…”
Section: Degree-of-polarisation Methodsmentioning
confidence: 99%
See 3 more Smart Citations